Implementation Of Small And Medium Enterprise Development In Indonesia As An Impact Of The Government's Budget Efficiency Policy (Case Study In East Nusa Tenggara) - Sari Bandaso Tandilino; Imelda R. Pelokila (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Indonesia focuses on efforts to support the development of SMEs because this sector provides 99.9% employment with 96.9% labor absorption, and Contribution to Indonesia's Gross National Product of 60.5% and the national entrepreneurship ratio has only reached 3.47% of the productive population in Indonesia, however, with the existence of budget efficiency policies, it will have an impact on the performance of SMEs. The purpose of the research is to find out the implementation of the development of East Nusa Tenggara MSMEs as an impact of government budget efficiency policies . The research method is carried out through several stages, namely the author observes and analyzes based on the phenomena that occur related to the research topic. Then determine the focus of the research based on the information that has been obtained and obtained from literature review and secondary data and other data and presented in the form of qualitative analysis. Result this research are government budget efficiency will have a positive impact on MSMEs if the saved funds are strategically reallocated to support key MSME development programs. Conversely, efficiency without careful consideration of the needs of the real sector can harm MSMEs and slow local economic growth.